A Case of Recurrent Hemorrhages due to a Chronic Expanding Encapsulated Intracranial Hematoma - Akiko Marutani; Kiyoshi Nagata; Jun Deguchi; Yuji Nikaido; Syuji Kazuki (Case Reports in Neurology, 2015)
Few case reports of encapsulated intracranial hematoma (EIH) exist, and the mechanisms underlying the onset and enlargement of EIH remain unclear. Here, we report on a 39-year-old woman with an EIH that repeatedly hemorrhaged and swelled and was ultimately surgically removed. In June 2012, the patient visited her local doctor, complaining of headaches. A magnetic resonance imaging (MRI) scan identified a small hemorrhage of approximately 7 mm in her right basal ganglia, and a wait-and-see approach was adopted. Six months later, her headaches recurred. She was admitted to our department after MRI showed tumor lesions accompanying the intermittent hemorrhaging in the right basal ganglia. After admission, hemorrhaging was again observed, with symptoms progressing to left-sided hemiplegia and fluctuating consciousness; thus, a craniotomy was performed. No obvious abnormal blood vessels were observed on the preoperative cerebral angiography. We accessed the lesion using a transcortical approach via a right frontotemporal craniotomy and removed the subacute hematoma by extracting the encapsulated tumor as a single mass. Subsequent pathological examinations showed that the hematoma exhibited abnormal internal vascularization and was covered with a capsule formed from growing capillaries and accumulating collagen fibers, suggesting that it was an EIH. No lingering neurological symptoms were noted upon postoperative follow-up. This type of hematoma expands slowly and is asymptomatic, with reported cases consisting of patients that already have neurological deficits due to progressive hematoma growth. Our report is one of a few to provide a clinical picture of the initial stages that occur prior to hematoma encapsulation.